Strategi Guru Dalam Memanfaatkan Pembelajaran Berbasis Digital pada Kurikulum Darurat COVID-19 - Sofyan Iskandar; Primanita Sholihah Rosmana; Ai Siti Nuratilah; Amelia Putri Cahyani; Moch Deannandra Fazrian (AS-SABIQUN, 2022)
The emergence of the Covid-19 pandemic has affected the education system in various parts of the world including Indonesia. These influences include changing the education system where schools are required to continue to run in a new situation, namely the Covid-19 pandemic. The learning carried out is required to adjust to the existing circumstances by the way distance learning (PJJ) is implemented. According to the results of literature studies that have been conducted that the teacher's strategy in utilizing digital-based learning in the Covid-19 emergency curriculum began to be applied in schools at every level of education ranging from elementary school to high school / vocational school. This research was conducted using qualitative descriptive methods that aim to determine the influence of technology on learning, the reasons why mastery of technology is very important, and to know the challenges and obstacles experienced by teachers and students in the application of this emergency curriculum. By knowing these things, therefore the use of good technology must be mastered by teachers in order to be able to create innovations in learning so that the implementation of this emergency curriculum can be maximized in its implementation.